Studi Komparasi Program Pembelajaran antara SMA Negeri di Kabupaten Purworejo dengan Kebumen - Anjani, Nesi; Widoyoko, Sugeng Eko Putro; Setiaji, Cahyo Apri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is prompted by the implementation of the Deep Learning (DL) approach pursuant to the Decree of the Minister of Primary and Secondary Education (Permendikdasmen) Number 13 of 2025. This study aims to: (1) determine the success of DL implementation in state senior high schools (SMA Negeri) across Purworejo and Kebumen Regencies, (2) compare the degree of implementation success between the two regencies, and (3) analyze the key challenges encountered during its implementation. This evaluation study employs a descriptive-comparative approach utilizing the CIPP evaluation model. The research was centered at SMAN 1 Purworejo and SMAN 1 Prembun. The target population comprised 755 tenth-grade students, from which a sample of 262 students was derived using Slovin's formula and selected via cluster random sampling. Economics subject teachers were also involved as interview respondents. Data collection techniques included questionnaires, document analysis, and interviews. Quantitative data were analyzed using descriptive analysis and an independent samples t-test assisted by SPSS software. The results indicate that: (1) the implementation of the DL program at SMAN 1 Purworejo and SMAN 1 Prembun achieved mean scores categorized as "good," at 3.06 and 2.80, respectively; (2) the independent samples t-test yielded a significance value (p-value) of 0.000 (< 0.05), indicating a statistically significant difference in DL program implementation between the two regencies, with a mean score difference of 0.26; and (3) the primary implementation challenges encompass instructional schedule management, student participation rates, restricted access to information, required educator competencies, and novel administrative adjustments.